Structural Studies and Ionic Transport Properties of Solid Biopolymer Electrolytes Based on Chitosan/ Methyl Cellulose Blend Doped with BMIMTFSI - Misenan M.S.M.; Khiar A.S.A. (Trans Tech Publications Ltd, 2024)
Indexed by SCOPUS/ERA